Monetary Policy and COVID-19. An Interview with Peter Tillman - Tillman, Peter (Revista Intercambio, 2020)
Peter Tillmann holds a Ph.D. in economics from the University of Cologne through the empirical analysis of international financial markets with modern time-series econometric techniques. His research interests are mainly monetary theory and policy; international macroeconomics and financial markets; and time series econometrics. Currently, Dr Tillmann is professor of Monetary Economics at Justus-Liebig-Universität Giessen. Previously, Dr. Tillman worked as a Senior Economics at the Economic Activity Department of the Swiss National Bank in Zurich. Source: Justus-Liebig-Universität Giessen